APLIKASI PERAMALAN PERMINTAAN BAHAN BAKU PADA PT. BABA RAFI INDONESIA DENGAN METODE PEMULUSAN EKSPONENSIAL WINTER (STUDI KASUS DAERAH SURABAYA) - Lumban Gaol, Luci Anna; Tjandrarini, A. B.; Sulistiowati, Sulistiowati (Jurnal JSIKA, 2013)
Abstract: PT. Baba Rafi Indonesia is a fast food franchise company, typical of the Middle East, which is now more widely known. Besides the franchise, PT. Baba Rafi Indonesia also provides raw materials to supply all outlets throughout Indonesia. Warehouse which located in Surabaya can supply approximately 20 outlets. The large number of outlets and demand for raw materials which are uncertain, make the Division of Logistics warehouse in Surabaya often face problems in providing raw material for franchises and outlets. Problems can be solved by use the forecasting application to determine the amount of raw materials that must be provided in Surabaya warehouse. Forecasting application was made from data collection, data preparation, and build application model. Based on the results of data collection, obtained pattern of the data which is tend seasonal and trend so applications forecasting use Exponential Smoothing Winter method. The next phase is implementing and evaluating applications that have been designed, whether running as expected or not. Forecasting application that was created can help Logistics Division to determine the amount of raw materials that must be provided in Surabaya warehouse based on past demand data. Report of forecasting results and list the amount of raw materials that must be purchased is expected to meet the demand for franchise and independent outlets. Keywords: forecasting, demand, exponential smoothing winter